Melahirkan Kembali Ulama Perempuan di Indonesia: Refleksi atas Kelangkaan Ulama Perempuan di Indonesia - Isnatin Ulfa (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2012)
Women discrimination judges as a reason of rare of women ula>ma>. Muhammad saw, in early Islam, places women as men as well; they can improve their intellectuality, can express amount of activities freely. Nevertheless, phases after Muhammad death, The condition goes back significantly. This condition reduces women’s role both at domestic aspect and at public areas such as education and other works and activities. It is real that nowadays, there are fiercely few women ula>ma>’ who work at an intellectual atmosphere including intellectual works, a political world, and a social sphere. Patriarch culture ”˜drives’ to this condition. Men’s oriented interpretation of religious texts gives also this condition worse because of its bias. This bias of interpretation reduces women rights. ”˜Women Perspective’, as a solution, can probably produce not only more fair religious law but also indiscriminative texts. Islamic world should ”˜open’ and give women rights as human to raise their intellectual quality and to give birth of new women ula>ma>’.